Pseudowords and guessing in the Yes/No format vocabulary test. (January 2020) - Zhang, Xian; Liu, Jianda; Ai, Haiyang
The main purpose of this study is to investigate guessing in the Yes/No (YN) format vocabulary test. One-hundred-and-five university students took a YN test, a translation task and a multiple-choice vocabulary size test (MC VST). With matched lexical properties between the real words and the pseudowords, pseudowords could index guessing in the YN test as correlations between false alarms and real word guessing were high (> .80). This finding provides important validity evidence for correction formulas that employ false alarm information to adjust the YN test scores. Another important finding is that the neighborhood size of pseudowords was related to false alarm rates, which has useful implications for the designing of future YN tests. Finally, the corrected scores of the YN test correlated highly (> .70) with those of the translation task. In comparison, correlations between the YN corrected scores and the MC VST scores were lower, indicating a difference in guessing between the two tests.